Evaluación radiográfica de la posición del hueso hioides en pacientes con relación esquelética Clase III según su patrón vertical - Aguilar Bautista, Kelly (2018)
Objective: To determine whether or not exists difference in the hyoid bone position between patients with skeletal class III according to its vertical pattern. Methods: This study included 102 lateral cephalograms belonging to skeletal Class III subjects aged 7-17 years old, selected from the Orthodontics and Maxillofacial Orthopedics Department at Children’s National Health Institute, taken between 2014 and 2016. Six variables were studied to determine the hyoid bone position, according to the Frankfurt Mandible Angle (FMA) value: Group I (n=57; FMA=21°-29°) and group II (n=45; FMA≥30°). Results: The average values for variable Perpendicular distance from Hpoint to Pterygoid perpendicular plane (H-PTRper) were 3.44 ± 6.89 mm for group I and -1.66 ± 6.75 mm for group II; Perpendicular distance from Hpoint to Sella perpendicular plane (H-Sper), 19.38 ± 7.17 mm and 13.37 ± 7.27 mm respectively; Perpendicular distance from Hpoint to horizontal plane of third cervical vertebra (H-C3Chor), -14.96 ± 6.04 mm and -17.12 ± 6.64 mm; Perpendicular distance from Gpoint to horizontal plane of third cervical vertebra (G-C3Chor), -5.64 ± 6.09 mm and -5.23 ± 6.43 mm; Angle between H-axis and Pterygoid perpendicular plane (Haxis-PTRper), 71.07 ± 7.71º and 65.64 ± 8.43º; Angle between hyoid axis and horizontal plane of third cervical vertebra (Haxis-C3Chor), 18.92 ± 7.67º and 24.19 ± 8.39º. Conclusions: It was determined that hyoid bone position in esqueletal Class III subjects differs according to the facial grown pattern, being more posterior and with a higher clockwise inclination in hiperdivergent patients. There was no significant difference in vertical hyoid bone position.